Analisis Isi Infografis Berita Kekerasan Seksual Pada Portal Berita Online Tirto.id - Abdul Salam, Nadia Febrianti; Latief, Rahmawati; Halik, Abdul; Mursalim, Muhammad Akram (Jambura Jurnal Ilmu Komunikasi, 2023)
Tirto.id is one of the online media that uses visual data journalism. Sexual violencecases are one of the topics discussed in this media by using infographics in describing importantfacts and data in the news. Purpose:This research aims to determine trends in media reportingpresented in the form of infographics regarding cases of sexual violence on the online news portalTirto.id. Methods:This research uses quantitative descriptive methods with content analysismethods. This research corpus consists of 20 infographics on sexual violence news from theonline news portal Tirto.id. Results: The results of this research show that 82.5% of theinformation sources for information on sexual violence news infographics came from nongovernmental institutions, namely Tirto.id Research, BKBLII, Walhi Sulteng, BailurangReportage, Sikola Mombine, The Jakarta Post Reportage, then 12.5% came from The governmentis the Ministry of Women's and Children's Empowerment, the National Commission for AntiViolenceAgainstWomenand5%acombinationofbothsources.Thetypesofsexualviolence experiencedbythevictimswere60%imagined,30%expressedverballyintheformofcatcalling, 7.5%expressedphysical,namelyunwantedtouchingleadingtoimmoralactssuchastouching thevictim'svitalorgans,and2.5%expressedvisualdistributionofphotosorcontentofvictims with sexual nuances without consent. 67.5% of efforts to handle and resolve cases of sexualviolence come from non-governmental institutions such as beauty brand product collaborationsholding campaigns and outreach regarding sexual violence, and 32.5% from the Government inthe form of legal regulations regarding the Sexual Violence Crime Law regarding the PKS Bill.(Elimination of Sexual Violence). Lastly, the types of infographics are 80% informational, 15%Timeline and 5% Mixedchart. Conclusion: The results of this research show that Tirto.id alwaysprioritizes news with clear, in-depth information sources in accordance with its research eventhough it is faced with the characteristics of modern journalism in the era of speed and artificialintelligence (AI).